CORROSION BEHAVIOR OF LOW ALLOY Ni-Cr-Mo STEEL AFTER HOT FORGING FOLLOWED BY INTERCRITICAL HEATING FOR WEATHERED RESISTANT FASTENER - Miftakhur Rohmah; Gusti Galih Pandhita; Septian Adi Chandra (Jurnal Rekayasa Mesin, 2022)
Low Ni-Cr-Mo alloys is developed by thermomechanical process to obtain high strength, toughness, and great hardenability properties. the aim of this study is to determine the correlation between the microstructure and corrosion properties after hot forging and followed by intercritical heating with cooling rate variation. Low Ni-Cr-Mo steel was homogenized,  hot forgings at 950℃, and heat treated at 880℃ with three cooling variations by water, oil, and air. Intercritical heating makes a dual-phase structure. Metallorgaphy and hardness test is confirmed a mechanical properties. OCP and cyclic polarization test is confirmed a corrosion behavior. As the fast-cooling (water quenchant) show the lath martensite, bainite, and a few of acicular ferrite. The hardness of the 75-ton result is slightly lower than the 50-ton load, is reached 591±9.4 VHN for 75-ton and 597±15.6 VHN for 50-ton. Polarization test resulted corrosion resistance sample with 100 ton forging water quench has a high corrosion rate 0.8 mpy, higher than air quench 0.01 mpy.